Research of Bearing Compound Fault Diagnosis based on EEMD and Hilbert Envelope Analysis - Yan Tianxiao; Zhang Ruiliang; Wang Tie; Jiang Xiongfei (Jixie chuandong)
In view of bearing compound fault of the low signal-to-noise ratio of the gear transmission system,firstly,the fault signal is decomposed to the order of IMFs and residue. Taking the kurtosis as characteristic index,the kurtosis value of the IMF components is calculated and the IMF component which has the maximum kurtosis is demodulated by Hilbert envelope. The final result shows that the method can effectively improve the signal-to-noise ratio,the bearing fault characteristic frequency can be extracted from strong background noise of gear transmission system.